Integrative conjugative elements of the ICEPan family play a potential role in Pantoea ananatis ecological diversification and antibiosis - De Maayer, Pieter; Chan, Wai-Yin; Martin, Douglas A. J.; Blom, Jochen; Venter, Stephanus N.; Duffy, Brion; Cowan, Don A.; Smits, Theo H. M.; Coutinho, Teresa A. (Frontiers in Microbiology, 2015)
Pantoea ananatis is a highly versatile enterobacterium isolated from diverse environmental sources. The ecological diversity of this species may be attributed, in part, to the acquisition of mobile genetic elements. One such element is an Integrative and Conjugative Element (ICE). By means of in silico analyses the ICE elements belonging to a novel family, ICEPan, were identified in the genome sequences of five P. ananatis strains and characterized. PCR screening showed that ICEPan is prevalent among P. ananatis strains isolated from different environmental sources and geographic locations. Members of the ICEPan family share a common origin with ICEs of other enterobacteria, as well as conjugative plasmids of Erwinia spp. Aside from core modules for ICEPan integration, maintenance and dissemination, the ICEPan contain extensive non-conserved islands coding for proteins that may contribute towards various phenotypes such as stress response and antibiosis, and the highly diverse ICEPan thus plays a major role in the diversification of P. ananatis. An island is furthermore integrated within an ICEPan DNA repair-encoding locus umuDC and we postulate its role in stress-induced dissemination and/or expression of the genes on this island.